Peningkatan Kemampuan Numerasi dengan Penerapan Metode Bermain Berbantuan Media Kartu Angka dan Stik Angka pada Siswa Kelompok A TK Al Hidayah II Kecamatan Taman Kota Madiun : Improving Numeracy Skills By Applying A Play-Based Method Using Number Cards And Number Sticks For Students In Group A At Al Hidayah Ii Kindergarten, Taman District, Madiun City - Istiqomah Setyaningsih; Ibadullah Malawi; Nurhadji Nugraha (Universitas Ngudi Waluyo, 2026)
The early numeracy skills of students in Group A at Al Hidayah II Kindergarten in Taman Kota Madiun District are still low, with 47% of students in the Not Yet Developed category and 53% in the Beginning to Develop category. This low level of skill is thought to be due to monotonous learning and a lack of interesting media. This study aims to address this problem by improving numeracy skills through the application of a play-based method using number cards and number sticks. This study used a Classroom Action Research (CAR) design conducted in two cycles. The results showed a significant improvement, with the percentage of success in numeracy skills increasing from 39.2% (pre-cycle) to 57.1% (Cycle I with number cards) and reaching 73.8% (Cycle II with number sticks). Indicators of ability such as showing, naming, ordering, and matching symbols for numbers 1-10 showed progress. The conclusion of this study is that the application of the play method assisted by number card and number stick media has been proven effective in improving numeracy skills. This media creates active, fun, and contextual learning, thereby helping young children understand number concepts. The implication is that the use of concrete and varied learning media is highly recommended for numeracy development at the kindergarten level. ABSTRAK Kemampuan numerasi awal siswa Kelompok A TK Al Hidayah II Kecamatan Taman Kota Madiun masih rendah, dengan 47% siswa berada dalam kategori Belum Berkembang dan 53% pada kategori Mulai Berkembang. Rendahnya kemampuan ini diduga akibat pembelajaran yang monoton dan kurangnya penggunaan media yang menarik. Penelitian ini bertujuan untuk mengatasi masalah tersebut dengan meningkatkan kemampuan numerasi melalui penerapan metode bermain yang dibantu media kartu angka dan stik angka. Penelitian ini menggunakan desain Penelitian Tindakan Kelas (PTK) yang dilaksanakan dalam dua siklus. Hasil penelitian menunjukkan peningkatan yang signifikan, dimana persentase keberhasilan kemampuan numerasi naik dari 39,2% (prasiklus) menjadi 57,1% (Siklus I dengan media kartu angka), dan mencapai 73,8% (Siklus II dengan media stik angka). Indikator kemampuan seperti menunjukkan, menyebutkan, mengurutkan, dan memasangkan lambang bilangan 1-10 mengalami kemajuan. Simpulan penelitian ini adalah penerapan metode bermain berbantuan media kartu angka dan stik angka terbukti efektif meningkatkan kemampuan numerasi. Media ini menciptakan pembelajaran yang aktif, menyenangkan, dan kontekstual, sehingga membantu pemahaman konsep bilangan pada anak usia dini. Implikasinya, penggunaan media pembelajaran konkret dan variatif sangat disarankan untuk pengembangan numerasi di tingkat TK.